Pemetaan Kompetensi Pedagogik Pendidik Kelompok Bermain Di Kecamatan Bumiayu Kabupaten Brebes Tahun 2014 - Eko Sulistyasih (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
Abstract: The purpose of this study was to map the pedagogical competence of playgroup (KB) educators in kecamatan Bumiayu in 2014. The results of the mapping can be used to determine how the quality of early childhood educators in kecamatan Bumiayu that can serve as a media controller quality ECD services. This study is a survey using a descriptive-quantitative approach. Data collected by using questionnaires, interviews, and documentaries. The collected data were then analyzed using the relative frequency distribution formula or percentage. Based on the results of research and discussion, pedagogic abilities KB educators in kecamatan bumiayu could be mapped as follows: (1) The result of the questionnaire showed that 44% of family planning educator in kecamatan bumiayu agree if they have pedagigic competence. (2) 45% of educator KB in kecamatan bumiayu agree if they have the ability to plan the educational program, parenting, and child protection. (3) 43% of educator KB in kecamatan bumiayu agree if they are able to carry out the process of education, care and protection. (4) 46% of educator KB in kecamatan bumiayu agree if they are able to carry out an assessment of the prosess and outcomes of education, care , and protection. Thus, the percentage of these four capabilities fall into the ‘quite well’ category. Keywords: pedagogical. educators, group play.